Hidden gateways to digital space : the spatial distribution of Wi-Fi networks in the context of demographic structure in rural areas - Janc, Krzysztof; Mazur, Marcin; Mazurek, Damian; Jurkowski, Wojciech; Wójcik, Marcin
Despite being seemingly invisible, digital space exerts a profound influence on society and economy. Similarly, the vast number of digital devices we use to access it – often invisible themselves – act as gateways to this realm. Identifying and mapping these hidden gateways to digital space can reveal the complexity of human activities functioning across real and digital spaces, and in between them. The conducted study aimed to identify spatial patterns in the distribution of Wi-Fi networks at a local scale in the context of demographic structure. It analysed the distribution of public and private Wi-Fi networks, which can be treated as hidden gateways to digital space. The spatial scope of this research encompassed rural areas of five Polish communes, chosen as representatives of different categories within the adopted typology. The main conclusion is that the spatial distribution of Wi-Fi networks is closely linked to the spatial distribution of younger age groups. This finding highlights issues related to the digital divide, particularly concerning varying digital competencies and needs. Additionally, it turns out that the strength of the relationship between people and Wi-Fi networks does not depend on the type of area or its specific characteristics.
Keywords: Wi-Fi networks; digital space; hidden gateways; rural areas; wardriving